Consensus Over Political Divisions: Polish Input in the Debate on Multiculturalism and Immigration to the European Union - Ciechański, Jerzy (Chrześcijaństwo-Świat-Polityka, 2024)
Multiculturalism as an ideology holds that Western societies ought to become mosaics of races, ethnicities and religions. At least from the mid-1980s, multiculturalism has set out the contents and limits of public debate and policy on immigration in Western democracies. That ideological supremacy has been effectively questioned only by the public reactions to the 2015 EU immigration crisis. Political rhetoric on immigration has changed more than actual policy. Meanwhile, in Poland, its deep political divisions notwithstanding, the mainstream elites of power and opinion have remained quite uniformly sceptical about the generally lax Western approach toward immigration, both regarding its ideological underpinnings and resulting policies. The scope of the Polish debate on immigration seems also much less constrained by the strictures of political correctness than has been the case in the West. The present article documents that transpolitical consensus, tracing its roots back to the historical experience specific to Poland and Central Europe.